The Economic Burden of Abortion and Its Complication Treatment Cares: A Systematic Review - Maryam Soleimani Movahed; Saeed Husseini Barghazan; Fariba Askari; Morteza Arab Zozani (Tehran University of Medical Sciences, 2020)
Objective: Abortion related procedures contribute to a significant economic burden because it resulted in prolonged hospital stays for patients. We aimed to gather available evidence on the economic burden of abortion and post-abortion complication treatment cares worldwide. Materials and methods: PubMed, Web of Science, Scopus, and Embase databases were searched through November 2019. Two researchers independently conducted the quality assessment and data extraction process. The latest web-based tool adjusted the estimates of costs expressed in one specific currency and price year into a specific target currency (the year 2016 $US). Results: Totally, 2082 records were retrieved and 32 studies were deemed eligible for qualitative synthesis. The mean total costs per patient with abortion or post-abortion care ranged from $23 to $564. The annual costs ranged from 189,000 $US to 134 million $US. Conclusion: Abortion and post-abortion care impose a substantial economic burden on society. Understanding the burdensome of abortion or pregnancy termination among policymakers provides vital information and enables informed decisions to be made to establish health care priorities and allocating scarce resources.